Status Kewarganegaraan Pelajar Keturunan Indonesia di Sanggar Bimbingan Kampung Bharu, Malaysia - Harahap, Siti Nur Halima; Nurhilmiyah, Nurhilmiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia is the fourth most populous country in the world. The population growth in Indonesia is not matched with job opportunities, so many Indonesians choose to work abroad. Malaysia is a country that receives a lot of Indonesian workers. Many of the Indonesian workers who have been working in Malaysia for a long time decide to settle down because they feel comfortable there. Moreover, many Indonesian workers marry fellow workers, resulting in children being born in Malaysia who are unable to obtain Malaysian citizenship because Malaysia follows the principle of jus sanguinis. This community service activity aims to help Indonesian students access education. The research problem in this study is how the citizenship status of Indonesian descent students in Sanggar Bimbingan Kampung Bharu Malaysia. The research method used is field research, which involves interviewing informants. The research results show that based on the cooperation between PCIM and KBRI in establishing Sanggar Bimbingan, even though it is informal and without special attire, students can learn and achieve their dreams even though they are still undocumented. Once students complete their education at Sanggar Bimbingan, they will receive a diploma that can be used in Indonesian schools so that students can continue their education up to a bachelor's degree and reach their dreams. Because every child has the right to education no matter where they are.